Lote da estação velha: ensaio sobre arquitectura evolutiva, flexível e adaptável - Sara Vale Guedes de Oliveira Teixeira (2016)
Given the exponential growth that the world population has shown, and the resulting high urban density, it becomes necessary to find flexible housing solutions that attend to each family's different needs and changes throughout their lives. Therefore, it is relevant to understand how the evolutionary process of mankind has influenced the evolution of architecture, from its nomadic times to the present. Thus, a historical and social review was made, offering an overview of the interconnection and interdependence between mankind and architecture throughout history, as well as the distinction of the different architecture types that arise from the use of flexible solutions: Evolutive Architecture, Flexible Architecture and Adaptable Architecture. To the effect of this dissertation, a research and subsequent designed and analytical listing of multiple case studies were made, including works of architects such as Le Corbusier, Renzo Piano or Shigeru Ban, so that a summary of the attributes and characteristics of evolutive, flexible and adaptable architecture that could be applied in a real project was elaborated. In order to achieve greater conceptual , geometric and dimensional knowledge, each case study was (re)designed in a valueadding process for the Lote da Estação Velha proposal.